Living with Inflammatory Bowel Disease: A Crohn’s and Colitis Canada Survey - Helen M Becker; Daniel Grigat; Subrata Ghosh; Gilaad G Kaplan; Levinus Dieleman; Eytan Wine; Richard N Fedorak; Aida Fernandes; Remo Panaccione; Herman W Barkema (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Despite improvements in therapies for inflammatory bowel diseases (IBDs), patient quality of life continues to be significantly impacted.